Burden and spectrum of neonatal surgical diseases in a tertiary hospital: a decade experience - Virupakshappa, Prashanth Madapura; Rajendra, Nidhi (International Journal of Contemporary Pediatrics, 2018)
Background: Surgical emergencies in the newborns are an important and integral part of neonatal admissions in any tertiary Neonatal intensive care units. Surgical emergencies in the newborn constitute congenital anomalies and acquired neonatal emergencies. It is necessary to know the burden of these illnesses and their spectrum by regular auditing the data available to understand the relative incidence and outcome of these neonatal emergencies. Aims and objective of the study is to determine the spectrum of the different neonatal surgical emergencies (congenital and acquired) admitted, operated and managed in a tertiary NICU from June 2001 to May 2011(10 yrs) in a medical college teaching hospital in South India Methods: The data was collected by retrospectively auditing the hospital pediatric and neonatal admission registry, neonatal surgical registry, admission case sheets from June 2001 to June 2011 (10 yrs). Data was analysed. Only confirmed post-operative surgical diagnosis were considered for inclusion in the study. Results: Of the 13,118 newborns admitted in the NICU in 10 years, 601 cases (4.6%) were surgical neonates which were treated in the unit. 83.5% of surgical neonates were operated for congenital surgical disorders. Gastrointestinal anomalies (50%) were the leading causes of neonatal surgical emergencies. Anorectal malformations (18.5%), idiopathic hypertrophic pyloric stenosis (10.6%) and esophageal atresia with/without tracheo-esophageal fistula (8.7%) were the leading surgical causes which needed immediate surgical intervention in the newborn period. 28 different spectrum of cases were operated including 15 rarer once (<1% incidence each). Conclusions: Surgical new-borns comprises of an important and integral part of neonatal admissions (4.6/100 neonatal admissions). The incidence of the rarer diseases constitutes 8% of the total surgical cases. Gastrointestinal anomalies are the leading causes requiring surgical interventions in the immediate newborn period. It is worthy to understand the spectrum of illnesses in any tertiary unit by regularly auditing the data available.